EFFECT OF BOARD CHARACTERISTICS ON CARBON EMISSION DISCLOSURE IN ENERGY AND AGRICULTURAL SECTOR COMPANIES - Chika, Joceline; Widianingsih, Luky Patricia (Berkala Akuntansi dan Keuangan Indonesia, 2024)
This study aims to examine the correlation between three dimensions of board characteristics, specifically, gender diversity, nationality diversity, and board independence with regards to carbon emission disclosure. This study adopted a quantitative approach utilizing multiple linear regression analysis. The sample consists of energy and agricultural firms which were listed on Bursa Efek Indonesia (BEI) between 2017 and 2021. Data were obtained from the annual and sustainability report of these companies. The research findings indicate that nationality diversity and board independence each possess a positive effect on carbon emission disclosure, whereas gender diversity does not show any influence. This study contributes to academic literature and offers an insight for any individuals concerned with carbon emission disclosure in Indonesia.